2006
DOI: 10.1128/aac.00869-05
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Live and Antibiotic-Killed Bacteria by Quantitative Real-Time PCR of Specific Fragments of rRNA

Abstract: Assessing bacterial viability by molecular markers might help accelerate the measurement of antibioticinduced killing. This study investigated whether rRNA could be suitable for this purpose. Cultures of penicillin-susceptible and penicillin-tolerant (Tol1 mutant) Streptococcus gordonii were exposed to mechanistically different penicillin and levofloxacin. Bacterial survival was assessed by viable counts and compared to quantitative real-time PCR amplification of either the 16S rRNA genes or the 16S rRNA, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 37 publications
1
48
1
Order By: Relevance
“…This scenario seems unlikely. The fact that DNA-based methods readily detect bacteria killed by antibiotics and other mechanisms (29,30) also makes it unlikely that abundant species were missed because of antibiotic killing.…”
Section: Antibiotic Treatment Does Not Likely Explain Differences Betmentioning
confidence: 99%
“…This scenario seems unlikely. The fact that DNA-based methods readily detect bacteria killed by antibiotics and other mechanisms (29,30) also makes it unlikely that abundant species were missed because of antibiotic killing.…”
Section: Antibiotic Treatment Does Not Likely Explain Differences Betmentioning
confidence: 99%
“…rRNA is also a more robust RNA species and will survive the extraction process at a considerably higher concentration than will mRNA 19 . Interestingly, the biodegradation kinetic profile of rRNAs has been shown to be similar to that of mRNAs, suggesting that rRNAs may serve well as a cell viability marker 20 . Since rRNAs are highly conserved among bacterial species, rRNA-based detection targeting the conserved sequences in the rRNA should provide universal coverage for all orthopaedically relevant bacterial species.…”
mentioning
confidence: 99%
“…The method gave results similar to the conventional colony counting method, but was not fully accurate. For some samples, it estimated viable cells over 10 times higher than of the conventional method 22) . Our method is thought to be reliable for quantitative detection of the target cell in a sample, but it needs an incubation procedure and more PCR reagents than a conventional real-time PCR procedure.…”
Section: Growth Of Salmonella Cell In Chickenmentioning
confidence: 99%
“…And the detection limit of it is as low as 10 1 CFU/mL 7) . On the other hand, Aellen et al 22) reported a method for viable target cell number by quantitative real-time PCR of specific fragments of rRNA. The method gave results similar to the conventional colony counting method, but was not fully accurate.…”
Section: Growth Of Salmonella Cell In Chickenmentioning
confidence: 99%
See 1 more Smart Citation